Pengaruh Jumlah Penduduk, Tenaga Kerja, Dependency Ratio dan Rasio Jenis Kelamin terhadap PDRB di Kota Banjarmasin - Muhammad Rafik; Khairi Pahlevi (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2020)
The objectives in this study are (1) to determine the effect of population on GRDP inBanjarmasin City; (2) to assess the impact of labor on GRDP in the city of Banjarmasin;(3) to determine the effect of the ratio of dependents to GRDP in the town of Banjarmasin;(4) to assess the impact of sex ratio on GRDP in Banjarmasin City; (5) To find out thesimultaneous influence of population, labor, dependency ratio, and sex ratio to GRDP inBanjarmasin City. And this research is expected to provide understanding to localgovernments, private parties, and community institutions with interest in economicdevelopment in the city of Banjarmasin through the GRDP and an overview of theirpopulation. This research can be a reference in the preparation of local governmentpolicies for economic development in Banjarmasin. This research method uses datacollection methods by taking data from the central static and related agencies. After that,multiple linear regression analysis is performed to see the effect of independent variableson the dependent. The software used for regression analysis is Eviews. This study'sresearch indicates that the population is having a significant impact and has a positiveinfluence on the GRDP of the City of Banjarmasin; the workforce and the ratio ofdependents do not substantially affect the GRDP of the City of Banjarmasin.